Body Position Affects Ultrasonographic Measurement of Diaphragm Contractility. Issue 4 (October 2018) - Brown, Christopher; Tseng, Shih-Chiao; Mitchell, Katy; Roddey, Toni
Abstract : Purpose: (1) Determine whether ultrasonography can detect differences in diaphragm contractility between body positions. (2) Perform reliability analysis of diaphragm thickness measurements in each test condition. Methods: We used a repeated-measures experimental design with 45 healthy adults where 3 B-mode ultrasound images were collected at peak-inspiration and end-expiration in supine, sitting, and standing. Mean diaphragm thickening fractions were calculated for each test position. Statistical significance was tested using 1-way repeated-measures analysis of variance with planned comparisons. For reliability analysis, the intraclass correlation coefficient (3, 3) was calculated. Results: Mean diaphragm thickening fraction increased from 60.2% (95% confidence interval [CI] 53.0%, 67.9%) in supine, to 96.5% (95% CI 83.2%, 109.9%) while seated and to 173.8% (95% CI 150.5%, 197.1%) while standing. Body position was a significant factor overall ( P < .001), as were comparisons between each individual position ( P < .001). Intraobserver reliability was excellent (>0.93) for all body positions tested. Conclusions: Ultrasound imaging detected positional differences in diaphragm contractility. The effect of gravitational loading on diaphragm length-tension, and body position-mediated changes in intra-abdominal pressure may explain the differences found. Future research should address methodological concerns and apply this method to patients participating in early mobilization programs in the intensive care unit.